REFRACTORY HYPERTENSION – MODERN APPROACHES TO DIAGNOSTICS AND TREATMENT - A. N. Britov; M. M. Bystrova (Рациональная фармакотерапия в кардиологии)
The refractory arterial hypertension (HT) is diagnosed, if therapy with three antihypertensive drugs from different classes (including a diuretic) in optimal doses did not provide target blood pressure (BP) level. Prevalence of a refractory HT is high and reaches up 10-30% among hypertensive patients. However, poor BP control is often caused by patient non-compliance with the medical recommendations, an inadequate estimation of BP level, and "white coat" HT. It is classified as a pseudo resistance. Obesity, salt and alcohol overconsumption, taking some drugs worsen BP control. Secondary HT causes (sleep apnea syndrome, kidney diseases, renal artery stenosis, and primary hyperaldosteronism) are more possible in patients with refractory HT. Specific treatment of these diseases improves BP control and long-term prognosis. Successful treatment of refractory HT includes detection and correction of reversible risk factors and reasons of the secondary HT, use of the effective combined therapy with the aldosterone antagonist. Improvement of patient compliance is one of key factors of effective treatment.